2012
DOI: 10.1111/j.1475-6773.2012.01431.x
|View full text |Cite
|
Sign up to set email alerts
|

The Urban‐Rural Disparity in Nursing Home Quality Indicators: The Case of Facility‐Acquired Contractures

Abstract: Objective. To identify and quantify the sources of the urban-rural disparity in facility-acquired contracture rates in nursing homes. Data Sources. Survey inspection data of U.S. nursing homes from 1999 to 2008 and standardized national rural definition file from the Rural-Urban Commuting Area Codes. Study Design. We estimated regressions of facility-level contracture rate as a function of urban-rural categories (urban, micropolitan, small rural town, and isolated small rural town) and other related facility c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 35 publications
0
39
1
Order By: Relevance
“…This indicates that our findings on the parent-to-offspring health transfer are robust to the elimination of unobserved family heterogeneity. 16 Compared with Tables 2A and 2B, the magnitude of the transmission stays about the same for mothers but is slightly lower for fathers, suggesting that the family heterogeneity is likely to correlate positively with the parents' and children's health. Furthermore, the signs and statistical significance of other control variables (such as the demographic, socio-economic and environmental characteristics) are also in line with the benchmark model.…”
Section: Random Effects Model Estimatesmentioning
confidence: 75%
“…This indicates that our findings on the parent-to-offspring health transfer are robust to the elimination of unobserved family heterogeneity. 16 Compared with Tables 2A and 2B, the magnitude of the transmission stays about the same for mothers but is slightly lower for fathers, suggesting that the family heterogeneity is likely to correlate positively with the parents' and children's health. Furthermore, the signs and statistical significance of other control variables (such as the demographic, socio-economic and environmental characteristics) are also in line with the benchmark model.…”
Section: Random Effects Model Estimatesmentioning
confidence: 75%
“…The literature has found that the markets for urban and rural nursing homes are structurally different and that rural nursing homes have lower level and quality of staffing (Bowblis et al 2013). In Appendix Table 2, we examine the impact of wage pass-through on staffing for rural nursing homes.…”
Section: Resultsmentioning
confidence: 99%
“…We also exclude Medicare only certified facilities, which do not serve Medicaid patients in the main analysis. Bowblis et al (2013) have found staffing patterns and the structure of the long term care market to differ considerably between urban and rural areas. We focus on urban nursing homes in the main analysis and present results for rural nursing homes in the appendix.…”
Section: The Nursing Home Data and Policy Variablesmentioning
confidence: 99%
“…Finally, we used the zip-code level rural urban commuting area file 30 to define rural versus urban location of the nursing home in order to capture possible rural-urban differences in care patterns. 31 …”
Section: Methodsmentioning
confidence: 99%